2013
DOI: 10.2139/ssrn.2276905
|View full text |Cite
|
Sign up to set email alerts
|

Emotional State and Market Behavior

Abstract: We consider the relationship between the emotional state of traders and market prices. We create asset markets with the structure first studied by Smith, Suchanek and Williams (1988), which is known to generate price bubbles and crashes. We analyze participants' facial expressions with facereading software before and while the market is operating. We find that greater positive emotion in facial expressions before the market opens predicts higher prices and larger bubbles. Greater fear predicts lower prices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Various studies stress the relevance of pre-market emotional states for market outcomes (Hargreaves Heap and Zizzo, 2011;Lahav and Meer, 2012;Andrade et al, 2015;Breaban and Noussair, 2013). Lahav and Meer (2012) and Andrade et al (2015) found that positivity and excitement respectively induce more pronounced overpricing in experimental asset markets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies stress the relevance of pre-market emotional states for market outcomes (Hargreaves Heap and Zizzo, 2011;Lahav and Meer, 2012;Andrade et al, 2015;Breaban and Noussair, 2013). Lahav and Meer (2012) and Andrade et al (2015) found that positivity and excitement respectively induce more pronounced overpricing in experimental asset markets.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of period 1, MIXLO participants report to feel borderline significantly more surprise (p = 0.103) and significantly more joy (p = 0.058). Remember that Lahav and Meer (2012) found that inducing positive mood before trading leads to higher deviations from fundamental values and thus larger levels of overpricing and that correlational studies also suggest such a relationship (Breaban and Noussair, 2013;Hargreaves Heap and Zizzo, 2011). Furthermore, at the end of the final trading period, MIXLO traders report significantly higher levels of excitement, fear and surprise than MIXHI participants (all p < 0.05).…”
Section: Increased Emotional Reactivitymentioning
confidence: 90%
See 2 more Smart Citations
“…Andrade, Odean, and Lin (2012) and Breaban and Noussair (2013) find that market bubbles increase in magnitude and amplitude when subjects are aroused or excited (induced by short videos before the SSW market). If arousal is, as in computer games, also lower in hybrid asset markets, then we should find smaller bubbles in hybrid markets than in human only markets.…”
Section: Human Computer Interactionmentioning
confidence: 99%